Les effets de l’émergence sur les discours officiels de promotion de la modernisation en Chine - Léo Kloeckner (EchoGéo)
Before the World Exposition in Shanghai, « spiritual civilization » visual campaigns (propaganda and public advertising images) had spread in publics spaces and residential areas throughout the city. They promote a new civilization of manners and public behaviors, referring to apparently globalized norms. Even though this visual discourse does not refer directly to the notion of emergence, it appears to be useful to explain the transformations in the production process of the official discourse. The way this discourse fits into the shanghainese urban space reveals the transformations that Chinese cities are undergoing in the context of an accelerated integration to globalization.